Pengaruh Promosi, Kualitas Pelayanan, dan Kemudahan Penggunaan Aplikasi Terhadap Keputusan Pembelian Go-Food di Kota Solo - Putri, Alvareza Kartika; Nurtantiono, Andri (ASSET: Jurnal Manajemen dan Bisnis, 2024)
Gojek is a familiar application used as one of the platforms for online food purchases through its service, Go-Food. The Gojek application is still in the first position based on the transaction value of food delivery services compared to its competitors so that this study will focus on examining the Go-Food feature owned by Gojek. The purpose of this study was to determine that there is an effect of Promotion, Service Quality, and Ease of Use of Applications on Go-Food Purchasing Decisions, especially in Solo City. From the questionnaires that have been distributed to 120 respondents, it can be shown that the results of research conducted using several data analysis instruments regarding the influence of Promotion, Service Quality, and Ease of Use of the Go-Food Application have a significant effect on Purchasing Decisions.Â Keywords: Promotion, Service Quality, Ease of Use, Purchase Decision, Gojek, Go-Food